The Effect of Olive Oil Therapy on Reducing Pruritus in Hemodialysis Patients - Indaryani Indaryani (Sekolah Tinggi Ilmu Kesehatan Sapta Bakti, 2026)
Background: Chronic Kidney Failure patients undergoing hemodialysis who experience pruritus are now widely discussed because it turns out this condition is not just a